2013
DOI: 10.3109/0284186x.2013.781674
|View full text |Cite
|
Sign up to set email alerts
|

Individualized positioning for maximum heart protection during breast irradiation

Abstract: Background. Prone positioning has been found feasible and appropriate for the reduction of radiation exposure of the lungs, but its effects on the heart dose remain controversial. individual anatomical features were sought for the selection of optimal treatment positioning. Material and methods. in 138 left-sided breast cancer cases awaiting postoperative whole-breast radiotherapy, conformal radiotherapy plans were generated in both prone and supine positions. Results. The radiation doses to the left anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 23 publications
3
52
0
Order By: Relevance
“…However, no studies have shown a statistically significant reduction in the mean heart dose between supine and prone free-breathing techniques. For example, Varga et al [36] reported mean heart doses of 2.9 Gy for supine three-dimensional conformal radiotherapy and 2.2 Gy for prone treatment (n ¼ 83, no significant difference), whilst Mulliez et al [35] reported mean heart doses of 2.0 Gy for supine inverse-planned multifield IMRT and 1.5 Gy for prone tangential field treatment (n ¼ 60, no significant difference). Furthermore, some authors advise caution based on the fact that the heart falls anteriorly when the patient lies face down [37], such that, in smallerbreasted women (C-cup and below) the prone position may even increase the heart dose as compared with supine freebreathing [10].…”
Section: Prone Breast Radiotherapymentioning
confidence: 95%
“…However, no studies have shown a statistically significant reduction in the mean heart dose between supine and prone free-breathing techniques. For example, Varga et al [36] reported mean heart doses of 2.9 Gy for supine three-dimensional conformal radiotherapy and 2.2 Gy for prone treatment (n ¼ 83, no significant difference), whilst Mulliez et al [35] reported mean heart doses of 2.0 Gy for supine inverse-planned multifield IMRT and 1.5 Gy for prone tangential field treatment (n ¼ 60, no significant difference). Furthermore, some authors advise caution based on the fact that the heart falls anteriorly when the patient lies face down [37], such that, in smallerbreasted women (C-cup and below) the prone position may even increase the heart dose as compared with supine freebreathing [10].…”
Section: Prone Breast Radiotherapymentioning
confidence: 95%
“…20,21 For comparison, the relative doses to the OARs were recorded as follows: the volumes of the ipsilateral breast receiving 4100%, 50%, and 25% of the prescribed dose (V 100% breast , V 50% breast , and V 25% breast ); the volume of the ipsilateral lung receiving 440% of the prescribed dose (V 40% lung ); the volume of the heart receiving 450% of the prescribed dose (V 50% heart , left-sided cases); the volume of the left anterior descendent (LAD) receiving 420% of the prescribed dose (V 20% LAD , left-sided cases); and the volume of the contralateral breast receiving 410% of the prescribed dose (V 10% opp breast ).…”
Section: Radiotherapy Techniquesmentioning
confidence: 97%
“…18 The target volumes were contoured on the computed tomography slices in the radiotherapy planning system by placing a 1-cm margin around the surgical cavity as defined by the surgical clips (clinical target volume), and using a 0.5-cm planning target volume (PTV) margin, but excluding the chest wall and the tissue 4 mm under the skin. 19 The OARs were contoured as previously described 20 ; the part of the operated breast excluding the PTV was indicated as "ipsilateral breast." The size of the PTV and the distance of its geometric center beneath the skin (D) were recorded.…”
Section: Radiotherapy Techniquesmentioning
confidence: 99%
“…Prone breast radiotherapy has proved feasible, and may be performed with good repositioning accuracy 3,6,7. Breast radiotherapy in either the prone or the supine position ensures good coverage of the operated breast, and similar dose homogeneity 3,4,8. Prone breast radiotherapy provides a long-term outcome (local/regional control and toxicity) similar to that of treatment in the supine position 9…”
Section: Introductionmentioning
confidence: 99%